The psychological conditions for employee engagement in organizational change: Test of a change engagement model - Albrecht, Simon L.; Furlong, Sarah; Leiter, Michael P. (Frontiers in Psychology, 2023)
In the contemporary world of work, organizational change is a constant. For change to be successful, employees need to be positive about implementing organizational change. Change engagement reflects the extent to which employees are enthusiastic about change, and willing to actively involve themselves in promoting and supporting ongoing organizational change. Drawing from Kahn’s engagement theory, the research aimed to assess the influence of change-related meaningful work, psychological safety, and self-efficacy as psychological preconditions for change engagement. The study also aimed to test the indirect associations of the change-related psychological preconditions with proactive work behavior through change engagement. Survey data from a Prolific sample (N = 297) were analyzed using confirmatory factor analysis and structural equations modeling. In support of the validity of the model, the results showed that change-related self-efficacy, psychological safety, and meaningfulness had significant direct effects on change engagement, explaining 88% of the variance. The change-related psychological conditions also had significant indirect effects on proactive work behavior through change engagement. The findings therefore suggest that employees who exhibit higher levels of change-related self-efficacy, psychological safety, and work meaningfulness are more likely to support and promote organizational change, and to proactively engage in innovative work behavior. In practical terms, organizations that create the psychological conditions for change could significantly improve employee motivation to change and to innovate, which in turn would increase the likelihood of successful organizational change, and improved organizational competitiveness. Study limitations and directions for future research are discussed.